Is methicillin-susceptible Staphylococcus aureus (MSSA) CC398 a true animal-independent pathogen? - Henok Ayalew Tegegne; Jean-Yves Madec; Marisa Haenni (Journal of Global Antimicrobial Resistance, 2022)
Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) belonging to ST398 has been widely described in animals. In parallel, methicillin-susceptible (MSSA) ST398 isolates causing severe infections in humans have recently emerged as animal-independent pathogens. This study aimed at characterising MSSA CC398 from different animal species in France in comparison with MSSA CC398 genomes, mostly of human origin. Methods: CC398 were detected by clone-specific PCR. Antimicrobial susceptibility testing was performed using the disk diffusion method. Whole genome sequencing (WGS) was performed on 47 MRSA and MSSA isolates, of which spa-types as well as resistance and virulence genes were extracted. A maximum likelihood phylogenetic tree based on SNPs was performed on all sequenced isolates and 51 additional MRSA and MSSA data found on publicly available databases. Results: From 275 MSSA isolates studied, 28 (10.18%) belonged to the CC398 lineage (26 ST398 and two single-locus variants) and mainly originated from cats (n=12/44, 27.3%) and dogs (n=8/55, 14.6%). Five different spa-types were identified, t571 (n=18, 64.3%) and t1451 (n=5, 17.9%) being the most frequent ones. Out of the 28 MSSA isolates, 26 carried the scn gene, whereas 24 carried the erm(T) gene, and all were genetically similar to human isolates. Conclusion: This study challenges the current scientific opinion that human infections due to MSSA CC398 should only be considered an animal-independent issue.